No Grammar, No Cry: Encouraging Confident English Communication: Pengabdian - Vivi Ayu Lestari; Anwar Hilman; Arif Budimansyah Purba; Ahmad Najib Mutawally; Rizki Teja Pratama; Ade Sofyan; Inpresta Natalia; Sekarlita Indriani; Cepi Indra Grahana; Juni Adi Putra (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Speaking is widely considered one of the most challenging skills for both university and high school learners, not primarily due to limited grammar or vocabulary, but because of psychological barriers such as fear of making mistakes and low self-confidence. This community service program, entitled “No Grammar, No Cry: Encouraging Confident English Communication,” aims to address these challenges by shifting learners’ focus from grammatical perfection to meaningful communication. The program was implemented through interactive workshops, peer conversation sessions, confidence-building games, real-life communication simulations, and mentoring activities to create a supportive and low-anxiety learning environment. A qualitative approach was employed to explore participants’ experiences, perceptions, and mindset changes during the program. Data were collected through participant reflections, observational notes, and informal discussions. The findings reveal that participants demonstrated increased willingness to speak, reduced speaking anxiety, and improved fluency and confidence in expressing ideas. In addition, learners developed a more positive attitude toward making mistakes, recognizing them as part of the learning process. Overall, the program highlights the importance of collaborative learning and experiential practice in fostering communicative competence. It also contributes to bridging the gap between theoretical knowledge and real-life communication, while promoting learner autonomy, sustained motivation, and adaptive communication skills.